Desarrollo de una metodología amigable con el ambiente para el pretratamiento de muestras de carne porcina - Rivera Mendiola, Florencia; Murcia, Vanina Nerea; Cora Jofre, Florencia; Savio, Marianela (COPROCNA, 2022)
Poster